Application of Game Theory in Determining the Optimal Winning Strategy for Presidential and Vice Presidential Candidates in the 2024 Election (Jurnal Matematika, Statistika dan Komputasi, 2024)
Game theory is applied in the context of the 2024 general election to determine effective strategies for each pair of candidates (paslon) presidential and vice presidential in the competition. This research yields several significant findings. In the match between paslon 1 and paslon 2, paslon 2 successfully secured victory with a score of -18, employing an optimal strategy focused on (candidate experience). Conversely, paslon 1 emerged victorious against paslon 3 with a score of 20, utilizing an optimal strategy based on (candidate vision and mission). In the final match between paslon 2 and paslon 3, paslon 2 once again achieved victory with a score of 36.88889. The optimal strategy for paslon 2 includes (candidate character), (candidate vision and mission), and (candidate experience). Paslon 3 also adopts a similar strategy. The results of this research provide insights into the development of candidate campaign strategies in the political competition context using a game theory approach.
Keywords: Game theory; optimal strategy; presidential candidate and vice presidential